Double Binds and Punchlines: An Examination of Women in Stand Up Comedy and Television Writers' Rooms - Sargent, Amberia (UCLA, 2019)
In this dissertation, I examine how double binds around sexuality and gender norms shape how women navigate sexual harassment and threats to their professional identities in stand up comedy and television writers’ rooms. I explain the ways the workplace dilemmas women confront are informed by race, sexuality, physical attractiveness, tenure, and relationship status.
Keywords: Sophie-Anne